Differential Corticomotor Excitability Responses to Hypertonic Saline-Induced Muscle Pain in Forearm and Hand Muscles - Dennis B. Larsen; Thomas Graven-Nielsen; Rogerio P. Hirata; Shellie A. Boudreau (Neural Plasticity)
Experimental muscle pain inhibits corticomotor excitability (CE) of upper limb muscles. It is unknown if this inhibition affects overlapping muscle representations within the primary motor cortex to the same degree. This study explored CE changes of the first dorsal interosseus (FDI) and extensor carpi radialis (ECR) muscles in response to muscle pain. Participants (n=13) attended two sessions (≥48 hours in-between). Hypertonic saline was injected in the ECR (session one) or the FDI (session two) muscle. CE, assessed by transcranial magnetic stimulation (TMS) motor-evoked potentials (MEPs), was recorded at baseline, during pain, and twenty minutes postinjection together with pain intensity ratings. Pain intensity ratings did not differ between the two pain sites (p=0.19). In response to FDI muscle pain, the MEPs of the FDI muscle were reduced at 2 and 4 min postinjection (p≤0.03), but not after ECR muscle pain. No significant MEP change was detected for the ECR muscle (p=0.62). No associations between MEPs and pain intensity were found (p>0.2). The present results indicate that the output from overlapping cortical representations of two muscles differentially adapts to acute muscle pain.